Applications of Kepler Algorithm-Based Controller for DC Chopper: Towards Stabilizing Wind Driven PMSGs under Nonstandard Voltages - Basiony Shehata Atia (21398774) (2024)
An optimization technique, the Kepler optimizer (KO), is presented to enable permanent magnet synchronous wind generators (PMSWG) to run safely under faults and to accomplish the goal of low-carbon efficient power delivery and sustainable development. Utility companies are struggling, which is preventing the increase in wind penetration, in spite of the grid incorporation of PMSWG. One of these undisputed concerns is the grid-side voltage dip (VD) and swell (VS) at the PCC. Converters and DCL capacitors are particularly vulnerable to PCC nonstandard voltages because of an imbalance in the DCL input–output powers. Because of this, it is essential to provide WF-GCs to support grid operations, and developing techniques to realize FRTCs has become a crucial GC need. Installing an industrial braking chopper (BC) across the DCL is the suggested technique, due to its effectiveness and low price. In addition, a new KO-based control system for BC is used to enhance its effectiveness. Four situations were examined to assess and analyze the proposed control system regarding the transient response of the system. These situations exposed the investigated system to an irregular grid condition: without BC, with BC controlled by a hysteresis controller, and with BC controlled by KO-based PI (proposed) at (a) 100% VD, (b) 70% VD, (c) 30% VD, and (d) 20% VS. To verify the advantages and efficacy of the suggested control systems in the examined circumstances, MATLAB/SIMULINK was utilized. The simulation findings confirmed the feasibility of the suggested system as a whole and the control structures in suppression of all parameter transient changes, while also achieving FRTC. Furthermore, maintaining a steady DCL voltage serves as an advantage that would lengthen the electrical converters’ lifetime and shorten the time that the unit would be turned off if it happens to fail. Other Information Published in: Sustainability License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.3390/su16072952